2017
DOI: 10.1002/jlb.2a0317-107r
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA networks associated with active systemic juvenile idiopathic arthritis regulate CD163 expression and anti-inflammatory functions in macrophages through two distinct mechanisms

Abstract: Summary sentence: MicroRNAs utilize multiple mechanisms to regulate CD163 expression and integrate well-characterized macrophage phenotypes and functional properties seen in active systemic juvenile idiopathic arthritis. AbstractSystemic juvenile idiopathic arthritis (SJIA) is a severe childhood arthropathy with features of autoinflammation. Monocytes and macrophages in SJIA have a complex phenotype with both pro-and anti-inflammatory properties that combine features of several well characterized in vitro cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…Cytokine concentrations in BAL fluid were determined using Milliplex Multiplex kits (MilliporeSigma) , except for IL‐18, which was determined using specific ELISA kits obtained from MBL.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokine concentrations in BAL fluid were determined using Milliplex Multiplex kits (MilliporeSigma) , except for IL‐18, which was determined using specific ELISA kits obtained from MBL.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, other reports have shown that CD163 + macrophages have anti-inflammatory M2 properties. The anti-inflammatory cytokine IL-10 was found to upregulate the expression of CD163 expression on macrophages (72). In addition, CD163 + macrophages are thought to play a protective role during inflammation due to their ability to clear free-hemoglobin (Hgb).…”
Section: Macrophages In Masmentioning
confidence: 99%
“…The miR-181s may target directly at CD163 mRNA for degradation. Overexpression of miR-181c inhibits the anti-inflammatory response of CD163 to hemoglobin or the high-mobility box 1 complex [ 110 ]. In contrast, transcriptome analysis of miR-125a-5p overexpression identified “cytokine–cytokine receptor interactions” as the most significantly inhibited gene pathway with reduced interleukin 10 Receptor Subunit Alpha ( IL10RA ), while IL-10 mediation is required for CD163 expression [ 108 ].…”
Section: Transcriptome Study Of Jiamentioning
confidence: 99%